Ubiquitous Social Networks: Opportunities and Challenges for Privacy-Aware User Modelling - Sören Preibusch; Bettina Hoser; Seda Gürses; Bettina Berendt (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Privacy has been recognized as an important topic in the Internet for a long time, and technological developments in the area of privacy tools are ongoing. However, their focus was mainly on the individual. With the proliferation of social network sites, it has become more evident that the problem of privacy is not bounded by the perimeters of individuals but also by the privacy needs of their social networks. The objective of this paper is to contribute to the discussion about privacy in social network sites, a topic which we consider to be severely under-researched. We propose a framework for analyzing privacy requirements and for analyzing privacy-related data. We outline a combination of requirements analysis, conflict-resolution techniques, and a P3P extension that can contribute to privacy within such sites.
Keywords: L86; C8; 330; World Wide Web; Privacy; Social Network Analysis; Requirements Analysis; Privacy Negotiation; Ubiquity; P3P; Datenschutz; Soziales Netzwerk; Internet; Virtuelle Gemeinschaft; Welt